Comparison of Standard and Enhanced Pulse Oximeter Auditory Displays of Oxygen Saturation: A Laboratory Study With Clinician and Nonclinician Participants. (October 2019) - Paterson, Estrella; Sanderson, Penelope M.; Brecknell, Birgit; Paterson, Neil A. B.; Loeb, Robert G.
Abstract : BACKGROUND: When engaged in visually demanding tasks, anesthesiologists depend on the auditory display of the pulse oximeter (PO) to provide information about patients' oxygen saturation (SpO2 ). Current auditory displays are not always effective at providing SpO2 information. In this laboratory study, clinician and nonclinician participants identified SpO2 parameters using either a standard auditory display or an auditory display enhanced with additional acoustic properties while performing distractor tasks and in the presence of background noise. METHODS: In a counterbalanced crossover design, specialist or trainee anesthesiologists (n = 25) and nonclinician participants (n = 28) identified SpO2 parameters using standard and enhanced PO auditory displays. Participants performed 2 distractor tasks: (1) arithmetic verification and (2) keyword detection. Simulated background operating room noise played throughout the experiment. Primary outcomes were accuracies to (1) detect transitions to and from an SpO2 target range and (2) identify SpO2 range (target, low, or critical). Secondary outcomes included participants' latency to detect target transitions, accuracy to identify absolute SpO2 values, accuracy and latency of distractor tasks, and subjective judgments about tasks. RESULTS: Participants were more accurate at detecting target transitions using the enhanced display (87%) than the standard display (57%; odds ratio, 7.3 [95% confidence interval CI, 4.4–12.3]; P < .001). Participants were also more accurate at identifying SpO2 range using the enhanced display (86%) than the standard display (76%; odds ratio, 2.7 [95% CI, 1.6–4.6]; P < .001). Secondary outcome analyses indicated that there were no differences in performance between clinicians and nonclinicians for target transition detection accuracy and latency, SpO2 range identification accuracy, or absolute SpO2 value identification. CONCLUSIONS: The enhanced auditory display supports more accurate detection of target transitions and identification of SpO2 range for both clinicians and nonclinicians. Despite their previous experience using PO auditory displays, clinicians in this laboratory study were no more accurate in any SpO2 outcomes than nonclinician participants.